How Functional Genomics Can Keep Pace With VUS Identification - Anderson, Corey L.; Munawar, Saba; Reilly, Louise; Kamp, Timothy J.; January, Craig T.; Delisle, Brian P.; Eckhardt, Lee L. (Frontiers in Cardiovascular Medicine, 2022)
Over the last two decades, an exponentially expanding number of genetic variants have been identified associated with inherited cardiac conditions. These tremendous gains also present challenges in deciphering the clinical relevance of unclassified variants or variants of uncertain significance (VUS). This review provides an overview of the advancements (and challenges) in functional and computational approaches to characterize variants and help keep pace with VUS identification related to inherited heart diseases.